The Matty Canyon Population: Dental Observations of Late Archaic Individuals from Southern Arizona - Lorrie Lincoln-Babb (Dental Anthropology Association, 1995)
Skeletal and dental material from the largest known burial population from the Late Archaic Period of southern Arizona was analyzed (Minturn and Lincoln-Babb, n.d.). Minturn performed the skeletal analyses, including the standard observations for age, sex, and pathologies. The dental analyses support a mixed economy subsistence of hunting-gathering and agriculture. This conclusion is based on observations for caries, enamel chipping, abscessing, and enamel hypoplasia.